2019
DOI: 10.19109/biota.v5i2.3359
|View full text |Cite
|
Sign up to set email alerts
|

Daily Activity of Male Mice (Mus musculus) in Laboratory

Abstract: The importance of observing the behavior of mice in the laboratory is additional information to compare with their behavior in nature and an effort to increase the welfare of mice (animal welfare) through alleviating the pain and suffering associated with scientific procedures. This study aims to study the daily activities of male mice in the laboratory. The method used was ad libitum and focal animal sampling. Based on the ad libitum sampling method, the daily activities of male mice in the laboratory were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The result of the observation on male mouse (Mus musculus) animal kept with female mouse showed that male individual carried out allogrooming activity to female mouse or to other male Oktiansyah (2015). Allogrooming is a physical activity (touch) carried out by at least two individuals of the same or different sex in one group with the aim of strengthening individual relationship between groups and easing tension between individuals during conflict (Matheson & Berstein, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The result of the observation on male mouse (Mus musculus) animal kept with female mouse showed that male individual carried out allogrooming activity to female mouse or to other male Oktiansyah (2015). Allogrooming is a physical activity (touch) carried out by at least two individuals of the same or different sex in one group with the aim of strengthening individual relationship between groups and easing tension between individuals during conflict (Matheson & Berstein, 2000).…”
Section: Introductionmentioning
confidence: 99%